Pengaruh Pola Asuh terhadap Perilaku Konsumtif Mahasiswa Penerima KIP Kuliah FISIP ULM - Rahmadi; Khairussalam (Huma: Jurnal Sosiologi, 2025)
Parenting patterns are suspected to influence the consumptive behavior of KIP-Kuliah scholarship recipients at the Faculty of Social and Political Sciences, Lambung Mangkurat University. This study aims to examine the impact of parenting on the consumptive behavior of economically disadvantaged students receiving KIP-Kuliah scholarships. It focuses on how parenting styles received since childhood affect students’ financial decision-making, particularly in managing their scholarship funds. Using a quantitative approach with a survey method, the study involved 133 KIP-Kuliah recipients from the 2023 cohort. Data were collected through questionnaires and analyzed using simple linear regression. Results show a significant influence of parenting patterns on consumptive behavior, with a probability value of 0.000 (< 0.05) and a constant of 12.737. The regression equation is Y = 12.737 + 0.552(X) + e. Parenting patterns account for 62.4% of the variation in consumptive behavior, while 37.6% is influenced by other unexamined factors. These findings confirm that parenting plays a critical role in shaping the consumptive behavior of KIP-Kuliah students. The study offers practical insights for parents to better guide their children's spending behavior and for program administrators to provide behavioral support alongside financial aid. Future research is encouraged to adopt qualitative case studies to enrich the understanding of how parenting influences financial behavior in this context.